Gtf2i and Gtf2ird1 mutation do not account for the full phenotypic effect of the Williams syndrome critical region in mouse models. (16th August 2019) - Kopp, Nathan; McCullough, Katherine; Maloney, Susan E; Dougherty, Joseph D
Abstract: Williams syndrome (WS) is a neurodevelopmental disorder caused by a 1.5–1.8 Mbp deletion on chromosome 7q11.23, affecting the copy number of 26–28 genes. Phenotypes of WS include cardiovascular problems, craniofacial dysmorphology, deficits in visual–spatial cognition and a characteristic hypersocial personality. There are still no genes in the region that have been consistently linked to the cognitive and behavioral phenotypes, although human studies and mouse models have led to the current hypothesis that the general transcription factor 2 I family of genes, GTF2I and GTF2IRD1, are responsible. Here we test the hypothesis that these two transcription factors are sufficient to reproduce the phenotypes that are caused by deletion of the WS critical region (WSCR). We compare a new mouse model with loss of function mutations in both Gtf2i and Gtf2ird1 to an established mouse model lacking the complete WSCR. We show that the complete deletion (CD) model has deficits across several behavioral domains including social communication, motor functioning and conditioned fear that are not explained by loss of function mutations in Gtf2i and Gtf2ird1 . Furthermore, transcriptome profiling of the hippocampus shows changes in synaptic genes in the CD model that are not seen in the double mutants. Thus, we have thoroughly defined a set of molecular and behavioral consequences of complete WSCR deletion and shown that genes or combinations of genes beyond Gtf2i and Gtf2ird1 are necessary to produce these phenotypic effects.